How Pinteresting: An Analysis of Social Media Resources for Internalizing Disorders. (September 2019) - San Jose, Alyssa L.; Hall, Cristin M.; Schaefer, Barbara A.; Breeden, Nicole C.
Many efforts have been made to understand social media and the resources existing online. However, prior studies have not thoroughly assessed specific platforms and the content being shared. The present study examined Pinterest content sharing as a proxy for interest among school personnel. Using Hall, Breeden, and Giacobe's coding scheme, 657 pins from 499 randomly selected pinners following the National Association of School Psychologists' Pinterest account were coded by content area and assessed for level of evidence base. Significant associations were found in chi-square analyses between category of internalizing disorders, evidence base, and types of pins shared. In addition, the category of internalizing disorder and level of evidence base were found to have a significant interaction with the ease of implementation. Assessing the content shared on Pinterest may inform future evidence-based implementation difficulties in schools.